RARE ASSOCIATION OF NEUROFIBROMATOSIS TYPE 1 WITH PRIMARY HYPERPARATHYROIDISM: A CASE REPORT - Ling, Melody Tsen Shu; Bin Mohd Diah, Mohd Idris; Ching, Tee Hwee (Journal of the ASEAN Federation of Endocrine Societies, 2022)
INTRODUCTION Neurofibromatosis Type 1 is an autosomal dominant genetic disorder characterized by central nervous system involvement, cutaneous manifestations and increased risk of developing endocrine-related tumors. Meanwhile, Primary Hyperparathyroidism is most commonly caused by parathyroid adenoma resulting in abnormal calcium homeostasis. There are case reports identifying an association between neurofibromatosis and primary hyperparathyroidism as a variant of multiple endocrine neoplasia (MEN) syndrome, however, their association is not fully understood. CASE This is the case of a 50-year-old male patient who is known to have neurofibromatosis type 1 with cutaneous manifestations (cafe au lait spots, neurofibromas, Lisch nodules) and pleural neurofibroma. He initially presented with persistent left lumbar pain and a kidney ultrasound demonstrated evidence of left nephrolithiasis. Laboratory tests revealed high serum calcium of 2.7 mmol/L to 3.1 mmol/L, a low phosphate level of 0.49 mmol/L and a markedly raised serum parathyroid hormone level of 1038 pg/ml. Vitamin D level was normal at 72.26 nmol/L and a calcium-to-creatinine-ratio of 0.019. Further workup with Sestamibi parathyroid scan revealed evidence of parathyroid adenoma inferior to the left thyroid gland. Contrast-enhanced computed tomography of the neck showed a heterogeneously-enhancing lesion in the same location corresponding with the Sestamibi scan finding. There was no clinical evidence of pheochromocytoma and the 24-hour urine metanephrines test was normal. With the imminent complication of nephrolithiasis, the patient is awaiting parathyroidectomy. CONCLUSION This case demonstrates a rare but proven co-occurrence between neurofibromatosis and primary hyperparathyroidism as evidenced by biochemical tests and radiographic imaging. Screening neurofibromatosis patients for primary hyperparathyroidism during the initial evaluation and follow-up is a potential step for early detection of the condition before it leads to complications.